2016
DOI: 10.1177/0263617416653120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the degree of infiltration of modified activated carbons with CuO/ZnO on the separation of NO2 at ambient temperatures

Abstract: The reduction of NO 2 in air at ambient temperatures with activated carbons can be increased by the infiltration of metal oxide nanoparticles into the sorbents. The NO 2 is first adsorbed to the activated carbon and subsequently catalytically reduced to physiologically neutral substances by the metal oxides. The catalytic reduction at ambient temperatures is rather slow. In a former study concerning the application in cabin air filters, it was shown that the modification of activated carbon with 5 wt% CuO/ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This interest leads to more research on the adsorptive separation of low concentrations of nitrogen oxides at ambient temperatures. In this context, Sager et al have examined the performance of different activated carbons in cabin air filter for the elimination of several pollutants [17][18][19][20][21]. In particular, authors examined the adsorption of low concentrations of NO 2 on modified activated carbon, prepared of polymer as base material, at ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interest leads to more research on the adsorptive separation of low concentrations of nitrogen oxides at ambient temperatures. In this context, Sager et al have examined the performance of different activated carbons in cabin air filter for the elimination of several pollutants [17][18][19][20][21]. In particular, authors examined the adsorption of low concentrations of NO 2 on modified activated carbon, prepared of polymer as base material, at ambient temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…They have showed that the elimination of NO 2 present in the air, on activated carbons at ambient temperature, and after repeated adsorption cycles, can be increased by the infiltration of metal oxide nanoparticles into the sorbent. In this case the regeneration of the filter was assumed to be connected to the redox properties of the sorbent that can act also as reduction catalyst towards NO x [18][19][20][21]. However, the role of surface chemistry of the activated carbon on the NO 2 adsorption/reduction was not examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes also justified that the appropriate pyrolysis and activation process enables the adsorbents' production within this scope [21]. Sager et al (2016) presented that NO2 gas reduction with the help of activated carbon can be advanced via metal oxide nanoparticles infiltration into sorbents at ambient temperatures. The adsorption of NO2was reduced in a catalytic way to physiological neutral substances through metal oxides after adsorbed by activated carbon.…”
Section: Industrial Processes 2%mentioning
confidence: 85%
“…The adsorption of NO2was reduced in a catalytic way to physiological neutral substances through metal oxides after adsorbed by activated carbon. The amount of reduction was quite slow at usual ambient temperatures [22].…”
Section: Industrial Processes 2%mentioning
confidence: 96%
“…In addition to the chemical modification of activated carbons, metals impregnation was studied in order to improve the adsorption capacity. Sager et al [ 20 ] reported on the influence of modified activated carbons with CuO/ZnO on the adsorption of NO 2 at room temperature. The authors have shown that the modification of activated carbon with 5 wt % CuO/ZnO leads to an increase of the NO 2 adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%